Find `int_(-1)^1 -e^x dx` using the Fundamental Theorem of Calculus. 1. S(superscript(1), subscript(-1)) -e^x dx and 2. S(superscript(4), subscript(1) sqrt(2/x) dx Thanks so much!!
- print Print
- list Cite
Expert Answers
calendarEducator since 2012
write1,275 answers
starTop subjects are Math and Science
To evaluate a definite integral, we need to use the Fundamental Theorem of Calculus. The formula is:
`int_a^b f(x) dx = F(x) | _a^b = F(b) - F(a)`
where F(x) is the anti-derivative of f(x).
So, determine the the antiderivative of `-e^x` . Apply the indefinite integral formula `int e^u du = e^u + C` .
`int -e^x dx= - int e^x dx = -e^x + C`
Hence, the antiderivative of `-e^x` is `-e^x` ` ` . Then, substitute this to the formula of Fundamental Theorem of Calculus to evaluate the given definite integral.
`int_(-1)^1 -e^x = -e^x | _(-1)^1 = -e^1 - (-e^(-1) )`
`= -e + e^(-1) = e^(-1) - e = 1/e - e`
Thus, `int_(-1)^1 -e^x = 1/e - e` .
Related Questions
- `int_(sqrt(2)/3)^(2/3) (dx)/(x^5 sqrt(9x^2 - 1))` Evaluate the integral
- 1 Educator Answer
- `int x/sqrt(x^2 + x + 1) dx` Evaluate the integral
- 1 Educator Answer
- Solve integral:`int (dx)/sqrt(1-e^(2x))`
- 2 Educator Answers
- integrate (1/(sqrt x)) (e^-x) dxI've got no idea how to do this.
- 1 Educator Answer
- Find the indefinite integral `int x sqrt((2x-1)) dx` using integration by substitution `int x...
- 1 Educator Answer
Unlock This Answer Now
Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.